Indonesia’s Multi-alignment Strategy: Explaining OECD Accession and BRICS Membership - Dewi Setiyaningsih; Thalassa Murti Jati; Anisa Rahmawati (Universitas Diponegoro, 2026)
This article examines Indonesia’s foreign policy under President Prabowo through the lens of neorealism. Amid intensification of geopolitical rivalries among great powers, Indonesia has actively pursued a strategy of multi-alignment. Drawing on neorealist assumptions, Indonesia’s foreign policy seeks to maximize national strategic autonomy through diversified bilateral and multilateral partnership. Indonesia demonstrates a pragmatic adaptation to structural constraints in the contemporary multipolar world order characterized by global political uncertainty; numerous middle power countries have started to respond by implementing multi-alignment strategy. Indonesia has taken the same initiatives. Under Prabowo’s leadership, Indonesia pursued BRICS membership and continued its OECD accession process as part of its economic and development cooperation initiatives. Notably, these two economic cooperation organizations represent two forces from opposing political blocs. This study examines Indonesia’s multi-alignment strategy under Prabowo’s leadership, with an emphasis on two significant policy moves in economic and development cooperation: OECD accession and BRICS membership. This study uses qualitative methods and draws on neorealist frameworks to investigate how Indonesia aims to enhance its global influence while maintaining its economic interest in the face of rising geopolitical rivalry between rich countries and the Global South. The findings show that Indonesia’s multi-alignment strategy is useful enough in securing Indonesia’s national interest.